2023
DOI: 10.1590/1519-6984.246312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant, photoprotective and antinociceptive activities of Marcetia macrophylla extract: potential for formulation of sunscreens

Abstract: The antioxidant, photoprotective and antinociceptive Marcetia macrophylla active extract was investigated as an active ingredient in a sunscreen cream formulation. Thus, the M. macrophylla extract showed IC50 of 3.43 mg/ml of the antioxidant (DPPH∙ scavenging test) and Sun Protection Factor of 20.25 (SPF/UV-B, at 250 µg/ml) and UV-A of 78.09% (photobleaching trans-resveratrol test). The antinociceptive activity was superior to all standards tested using the in vivo acetic acid-induced writhing test (99.14% at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Like this study, Costa et al [72] used the crude extract of Marcetia macrophylla in photoprotective formulations and observed that SPF values increased proportionally to the extract concentration in each formulation. Higher EC50 concentrations could result in an even more significant increase.…”
Section: Assessment Of Photoprotective Activitymentioning
confidence: 66%
“…Like this study, Costa et al [72] used the crude extract of Marcetia macrophylla in photoprotective formulations and observed that SPF values increased proportionally to the extract concentration in each formulation. Higher EC50 concentrations could result in an even more significant increase.…”
Section: Assessment Of Photoprotective Activitymentioning
confidence: 66%